Protocol to assess the effectiveness and safety of novel oral anticoagulants (NOAC) vs warfarin in real world settings: cohort study in primary care - Hippisley-Cox, Julia; Coupland, Carol (University of Nottingham, 2016)
Anticoagulants are used to treat thrombosis and to prevent thrombosis and stroke among those at high risk. Older anticoagulants such as warfarin can be effective but require regular monitoring and may lead to major bleeding and even death. Newer anticoagulants may not need blood tests but they are quite expensive. There is a lack of information on how safe these new treatments are in the longer term since the original trials were done over relatively short periods of time. Also the trials were done in selected patients who may be different from patients in real world settings. So there is a need to establish how safe the new anticoagulants are compared with the older ones when used in real world settings over longer periods of time. Our aim is use a large primary care research database (QResearch) to investigate the unintended effects of novel anticoagulants (NOACS) in primary care populations compared with warfarin. Our specific objective is to evaluate bleeding, stroke and thrombosis outcomes associated with NOACs (both individual drugs & class effect) compared with warfarin in NHS patients.